(untitled) (Journal of Scientific Research, 2012)
Cu-Zn ferrites of composition Cu1-xZnxFe2O4 were prepared by double sintering ceramic technique at 9500C and 10500C for 3 hours and 2 hours, respectively. Structural and magnetic properties of the Cu-Zn ferrites were investigated by using X-ray diffraction, microstructure study and complex permeability behaviour. X-ray analysis indicated the formation of single-phase cubic spinel structure for all samples. The lattice parameter was found to increase with increasing Zn content obeying Vegards law. The X-ray and bulk densities of the Cu-Zn ferrite significantly decreased whereas porosity increased with increasing Zn concentration. Micrographs exhibited decrease in grain size with increasing concentrations. The real part ?of initial permeability remained constant up to certain lower range of frequency after which it decreased to lower value of permeability. ? increased with increasing Zn contents up to x = 0.5, after that it decreased with higher Zn content but was also found to increase with sintering temperature. The possible reasons responsible for change in structural, microstructural and complex permeability with increasing of non-magnetic Zn2+ ion are ascertained. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.10798 J. Sci. Res. 4 (3), 551-560 (2012)